Umbilical Cord Care Knowledge and Practices of Mothers attending Selected Primary Health Care Centres in Ibadan, Nigeria (2020)
Background: Poor umbilical cord care (UCC) practices have been linked with infections and mortality in newborns. Some mothers use multiple agents in umbilical cord care. It is imperative to assess the knowledge of UCC and its practices among women at the lowest level of care. Methods: The study utilized a cross-sectional design. Multistage sampling technique was used to select 414 mother baby pairs (dyad) attending infant welfare clinics in the selected Primary Health Centres (PHCs). Data was collected using structured validated questionnaire after obtaining ethical approval and informed consent. Descriptive statistics were used for analysis of data and hypotheses were tested using chi-square statistic at p=0.05. Results: One hundred and ninety-nine (48.1%) of the respondents had a good level of knowledge of appropriate UCC, 254(61.4%) respondents practiced good cord care. Even though most (95.7%) mothers used methylated spirit to clean the cord, quite a number, 270(65.5%) applied mentholated balm to the umbilicus. Above 60% of those who received information on UCC had good practice compared to those that did not (p=0.04). Also, 125(62.8%) of the respondents with good knowledge of UCC had good cord care practices compared to 74(37.2) with poor practices. Respondents’ knowledge of UCC was not significantly associated with their cord care practices. Conclusion: Gaps were observed in both knowledge and practices of umbilical cord care among the mothers attending primary health care centres. Strategies need to be instituted by health care workers to improve knowledge of umbilical cord care and inappropriate practices should be strongly discouraged.